TRENDS OF PROFESSIONAL TRAINING OF SPECIALISTS IN EUROPEAN COUNTRIES: QUALITY ASSURANCE (IQA) SYSTEM IN HIGHER EDUCATION - Svitlana Zaskaleta (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article analyzes the problem of ensuring the quality of higher education. Ukraine aims to be in the European trend towards modernization of higher education. Ensuring the quality of higher education is much planned and at the same time the availability of the necessary resources (academic and administrative staff, students, academic and administrative leaders; financial, material, informational, scientific, educational resources etc.); organization of educational process that most adequately reflect modern trends in the development of national and world economy and education; the control of educational activities at the higher education sector and the quality of training of specialists at all stages of training and at all levels: the higher education institution, for higher education in different national and international (European) level. Quality assurance requires a lot of preparatory work. This is an extended process that requires continuous improvement of the achieved performance. The general tendency of professional training of specialists in the countries of the European space is determined. It is to ensure the quality of higher education. The quality assurance of higher education is governed by the legal framework of the countries (the Law on Higher Education and related by-laws). Higher education quality assurance tasks are carried out by the Agency for the Supervision and Quality Assurance of Higher Education, in accordance with EU legislation and recommendations in the field of higher education quality. It is noted that the mechanisms of quality assurance of higher education are constantly being improved, which is the key to the development of higher education systems in the countries of the European area. Quality assurance is a priority of the Bologna Process, but its mechanisms are not seen as a goal. Their ultimate goal is to improve the quality of teaching and research. The quality assurance bodies support the institutions in their further development and, equally, play a key role as defenders of the public interest. Key components of the quality assurance system of higher education is to ensure the quality of education at the Universities, processes of quality assurance in education teaching and learning; approval monitoring and periodic review of programs for assessing the quality of teaching staff, educational resources and support for students of information systems.